Sub-micron patterning of metal oxide surfaces via microcontact printing and microtransfer molding of amphiphilic molecules and antifouling application - Cordero Guerrero, Josué (2023)
Low cost, potentially scalable soft lithography approaches are employed here to generate nano and microscale line patterns of n-octadecylphosphonic acid and n-octadecyltriethoxysilane with thicknesses ranging from 2 up to 150 nm depending on conditions and substrates used. Elastomer stamps generated from commercial optical media (DVD-R and CD-R) are used to print the amphiphile n-octadecylphosphonic acid (ODPA) on mica, Si(111), and aluminum AA6063, while n-octadecyltriethoxysilane (OTES) is printed on AA6063. The thicker ODPA pattern generated via microtransfer molding is robust enough to act as resist for wet etch on aluminum alloy at its resolution limits, allowing a more permanent pattern directly on the substrate (resulting in a pitch of 1600 nm and crest full width half maximum of 820 nm). Upon surface modification with a non-polar terminated monolayer (post-patterning), the water contact angle is shown to increase relative to unpatterned hydrophobic control, resulting in significantly less bacteria adhesion.